Interplay of Matrix Stiffness and c-SRC in Hepatic Fibrosis - Görtzen, Jan; Schierwagen, Robert; Bierwolf, Jeanette; Klein, Sabine; Uschner, Frank E.; van der Ven, Peter F.; Fürst, Dieter O.; Strassburg, Christian P.; Laleman, Wim; Pollok, Jörg-Matthias; Trebicka, Jonel (Frontiers in Physiology, 2015)
Introduction: In liver fibrosis activation of hepatic stellate cells (HSC) comprises phenotypical change into profibrotic and myofibroplastic cells with increased contraction and secretion of extracellular matrix (ECM) proteins. The small GTPase RhoA orchestrates cytoskeleton formation, migration and mobility via non-receptor tyrosine-protein kinase c-SRC (cellular sarcoma) in different cells. Furthermore, RhoA and its downstream effector Rho-kinase also play a crucial role in hepatic stellate cells and hepatic fibrogenesis. Matrix stiffness promotes HSC activation via cytoskeleton modulation. This study investigated the interaction of c-SRC and RhoA under different matrix stiffness conditions. Methods: Liver fibrosis was induced in rats using bile duct ligation (BDL), thioacetamide (TAA) or carbon tetrachloride (CCl4) models. mRNA levels of albumin, PDGF-R, RHOA, COL1A1 and αSMA were analyzed via qRT-PCR. Western Blots using phospho-specific antibodies against p-c-SRC418 and p-c-SRC530 analyzed the levels of activating and inactivating c-SRC respectively. LX2 cells and hepatocytes were cultured on acrylamide gels of 1kPa and 12kPa or on plastic to mimic non-fibrotic, fibrotic or cirrhotic environments, then exposed to SRC-inhibitor PP2. Overexpression of RhoA was performed by transfection using RhoA-plasmids. Additionally, samples from cirrhotic patients and controls were collected at liver transplantations and tumor resections were analyzed for RhoA and c-SRC protein expression by Western Blot. Results: Transcription of albumin and RhoA was decreased, whereas transcription and activation of c-SRC was increased in hepatocytes cultured on 12kPa compared to 1kPa gels. LX2 cells cultured on 12kPa gels showed upregulation of RHOA, COL1A1 and αSMA mRNA levels. Inhibition of c-SRC by PP2 in LX2 cells led to an increase in COL1A1 and αSMA most prominently in 12kPa gels. In LX2 cells with RhoA overexpression, c-SRC inhibition by PP2 failed to improve fibrosis. RhoA expression was significantly elevated in human and experimental liver fibrosis, while c-SRC was inactivated. Conclusions: This study shows that c-SRC is inactive in activated myofibroblast-like HSC in liver cirrhosis. Inactivation of c-SRC is mediated by a crosstalk with RhoA upon hepatic stellate cell activation and fibrosis progression.